Corrosion Problems and Solutions in Oil Refining and Petrochemical Industry - Groysman, Alec.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book addresses corrosion problems and their solutions at facilities in the oil refining and petrochemical industry, including cooling water and boiler feed water units. Further, it describes and analyzes corrosion control actions, corrosion monitoring, and corrosion management. Corrosion problems are a perennial issue in the oil refining and petrochemical industry, as they lead to a deterioration of the functional properties of metallic equipment and harm the environment - both of which need to be protected for the sake of current and future generations. Accordingly, this book examines and analyzes typical and atypical corrosion failure cases and their prevention at refineries and petrochemical facilities, including problems with: pipelines, tanks, furnaces, distillation columns, absorbers, heat exchangers, and pumps. In addition, it describes naphthenic acid corrosion, stress corrosion cracking, hydrogen damages, sulfidic corrosion, microbiologically induced corrosion, erosion-corrosion, and corrosion fatigue occurring at refinery units. At last, fouling, corrosion and cleaning are discussed in this book.
Corrosion Problems in Oil Refining and Petrochemical Industry -- Crude oil -- Petroleum distillates -- Naphthenic Acids. Myths and Truth -- Stress Corrosion Cracking -- Hydrogen Damages -- Sulphur Corrosion -- Petrochemical Media -- Cooling Water Systems -- Boiler Feed  Water -- Microbiologically Induced Corrosion -- Erosion-Corrosion -- Corrosion Fatigue.-  Solutions and Corrosion Control at Oil Refinery Units -- Materials Compatible With Corrosive Media -- Technological Actions -- Corrosion Inhibitors and Neutralizers -- Coatings -- Cathodic Protection -- Corrosion Failure Cases and Their Prevention at Oil Refinery Units -- Corrosion Monitoring at Oil Refinery Units -- Anti-Corrosion Management at Oil Refinery Units -- Conclusion: Insight into Future.
Keywords: Coatings; Tribology; Corrosion and anti-corrosives.; Engineering design; Chemistry, Technical; Coatings; Tribology; Corrosion; Engineering Design; Industrial Chemistry